Determination of flow parameters in Mundoghat irrigation canal of Hirakud canal system using flow measuring instruments. (March 2019) - Rath, Ashutosh; Swain, Prakash Chandra
Highlights: ADV and micro ADV are used to find the discharge and turbulence characteristics of the flow. Reynolds' Shear stress and turbulent kinetic energy are also determined for flow. Performance evaluated with adequacy dependability, equity and the conveyance efficiency. Abstract: A major portion of Indian population depends upon agriculture. The irrigation canals play an important role in providing water to the plants for their turgidity. In this work an attempt is made to use relatively accurate instruments such as Flow Tracker ADV and micro ADV to calculate the discharge and the turbulence characteristics of the flow in Mundoghat canal, which take off from the power channel of Hirakud power house, India. The velocity was found to be 0.239 m/s using Flow Tracker ADV and 0.2518 m/s by using Micro ADV. The average Reynolds shear stress was found out to be 0.203 N/m 2 and the average turbulent kinetic energy 41.251 cm 2 /s 2 . A humble attempt is made to measure the performance of Mundoghat canal through various indicators. The values of indicators for the Mundoghat canal are adequacy of 82.69%, dependability 77%, equity of 86.3% and the conveyance efficiency of 89.76%.